2001
DOI: 10.1051/vetres:2001146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk sampling techniques on milk composition, bacterial contamination, viability and functions of resident cells in milk

Abstract: -Three different milk sampling techniques were evaluated during milk sampling: a direct aseptic collection from the udder through a sterile cannula was used as the reference technique, compared with either a manual or a mechanical sampling method. In this study 30 high-yielding HolsteinFriesian dairy cows at different stages of lactation and free of udder infection were used. For each milk sample, the influence of milk sampling techniques was determined for the following parameters: somatic cell count, milk co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…On the one hand, their concentration is too low for an efficient phagocytosis in suspension [95]. Moreover, part of them are nonviable or in the process of apoptosis, in particular in cisternal milk, and are not in an activated state [22,196,197]. On the other hand, the presence of neutrophils in the milk of healthy glands seems to correlate inversely with a risk of intramammary infections [22].…”
Section: Cellular Defensesmentioning
confidence: 99%
“…On the one hand, their concentration is too low for an efficient phagocytosis in suspension [95]. Moreover, part of them are nonviable or in the process of apoptosis, in particular in cisternal milk, and are not in an activated state [22,196,197]. On the other hand, the presence of neutrophils in the milk of healthy glands seems to correlate inversely with a risk of intramammary infections [22].…”
Section: Cellular Defensesmentioning
confidence: 99%
“…During this period a decrease in cell function of the PMN, resident in the healthy mammary gland Mehrzad et al, 2001;Vangroen-weghe et al, 2001) has been observed. The decrease in cell function was mainly related to the decrease in viability, oxidative burst, and intracellular killing by PMN Mehrzad et al, 2001; Vangroenweghe et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been shown to play a role in the clinical outcome of Escherichia coli mastitis, namely farm management (Smith et al, 1985;Schukken et al, 1989aSchukken et al, , 1989bOliver et al, 1990;Lam et al, 1995;Barkema et al, 1999), bacterial factors (Frost et al, 1980;Hill, 1981;Linton and Robinson, 1984;Sanchez-Carlo et al, 1984a;Sanchez-Carlo et al, 1984b;Todhunter et al, 1991;Hogan et al, 1992;Cross et al, 1993;Nemeth et al, 1994;Hogan et al, 1995Hogan et al, , 1999Nagy and Fekete, 1999), and physiological factors (Heyneman et al, 1990;Gilbert et al, 1993;Kremer et al, 1993aKremer et al, , 1993bVandeputte-Van Messom et al, 1993;Dosogne et al, 1997Dosogne et al, , 2001van Werven et al, 1997;Mehrzad et al, 2001Mehrzad et al, , 2002Vangroenweghe et al, 2001;Burton and Erskine, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There have been attempts to adapt those assays to milk PMN (Hoeben et al, 1997;Dosogne et al, 2001;Vangroenweghe et al, 2001Vangroenweghe et al, , 2002 but they are still expensive and time-consuming. Consequently, they cannot be applied in large-scale field studies, as required in programs of selection for mastitis resistance.…”
Section: Introductionmentioning
confidence: 99%